World faiths an introduction - Oliver, Paul (London Hodder Education, 2010)
A concise introduction to the major religions around the world. Covers the history of each faith, its core beliefs, and how it is practiced today.
"Previously published as Teach yourself world faiths"--Title page verso.
"Explores contemporary debates"--Cover.
Includes bibliographical references (pages [177]-178) and index.
Keywords: Religions